Non-small cell lung cancer with MET amplification: review of epidemiology, associated disease characteristics, testing procedures, burden, and treatments - Yang, Mo; Mandal, Erin; Liu, Frank X.; O’Hara, Richard M.; Lesher, Beth; Sanborn, Rachel E. (Frontiers in Oncology, 2024)
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer in the United States and is often diagnosed at an advanced disease stage. Guidelines recommend testing patients with advanced NSCLC for actionable genomic alterations, including the emerging biomarker, mesenchymal-epidermal transition factor (MET) gene amplification (METamp). METamp in advanced NSCLC may be primary (i.e., METamp is identified before initiating treatment) or secondary (i.e., METamp is identified during or following initial or subsequent treatment).We conducted a literature review to better understand the epidemiology, testing procedures, economic and humanistic burdens, practice patterns, and treatments under investigation for advanced METamp NSCLC. Results of our literature review demonstrated that primary METamp occurs in approximately 5% of NSCLC cases and secondary METamp occurs in approximately 15% of NSCLC cases previously treated with an epidermal growth factor receptor inhibitor (a treatment used for some patients with advanced NSCLC). Variability in testing methods and definitions of METamp were identified across identified studies. Several treatments have shown promise in treating METamp NSCLC. Additional studies evaluating the clinical, economic, and humanistic burden are needed.This review provides a needed, comprehensive overview of an emerging biomarker, METamp, in advanced NSCLC.